Нужно воспользоваться формулой разности квадратов практически во всех примерах: (a - b)(a + b) = a² - b².
Выполните умножение:
1) 5b(b - 1)(b + 1) = 5b(b² - 1) = 5b³ - 5b;
2) (c + 2)(c - 2) · 8c² = (c² - 4) · 8c² = 8c⁴ - 32c²;
3) (m - 10)(m² + 100)(m + 10) = (m - 10)(m + 10)(m² + 100) =
= (m² - 100)(m² + 100) = m⁴ - 10 000;
4) (a² + 1)(a² - 1)(a⁴ + 1) = (a⁴ - 1)(a⁴ + 1) = a⁸ - 1;
Упростите выражение:
1) (x + 1)(x - 1) - (x + 5)(x - 5) + (x + 1)(x - 5) = x² - 1 - (x² - 25) + x² - 5x + x - 5 = x² - 1 - x² + 25 + x² - 4x - 5 = x² - 4x + 19;
2) 81a⁸ - (3a² - b³)(9a⁴ + b⁶)(3a² + b³) = 81a⁸ - (3a² - b³)(3a² + b³)(9a⁴ + b⁶) = 81a⁸ - (9a⁴ - b⁶)(9a⁴ + b⁶) = 81a⁸ - (81a⁸ - b¹²) = 81a⁸ - 81a⁸ + b¹² = b¹².
а) 4sin³x -8sin²x -sinx +2 =0 ;
4sin²x(sinx-2) -(sinx -2) =0 ;
(sinx -2)(4sin²x -1) = 0 ⇔[ sinx -2 =0 ;4sin²x -1 =0.
sinx -2 =0⇔sinx =2 || > 1 →нет решения.||
4sin²x -1= 0 ⇔4*(1-cos2x)/2 -1 = 0 ⇔cos2x =1/2 ⇒2x =±π/3 +2πk , k∈Z.
ответ: ±π/6 +πk , k∈Z.
---
б) ;
(1-cos²x) -2cosx +2 =0 * * * можно заменить t =cosx , |t| ≤1 * * *
cos²x +2cosx -3 =0 ⇒[cosx = -3(не имеет решения) ; cosx =1.
ответ: 2πk , k∈Z.
-------
N2
а) ⇔ 7^(5x-1)(7 -1) =6⇔ 7^(5x -1)*6 =6⇔7^(5x -1) =1.
7^(5x -1) =7⁰ ⇒5x-1 =0 ; x =0,2.
---
б) ;
ОДЗ : { 2x+4 >0 ; 4x -7 >0 ; 4x -7 ≠1. ⇒ x∈(1,75 ;2) U(2 ;∞).
Lq(2x+4) =2Lq(4x-7)⇒Lq(2x+4) =Lq(4x-7)² ;2 x+4 =(4x -7)² ;
16x² -58x +45 =0 ;
D/4 =29² -16*45 =841 -720 =121 =11²
x₁= (29 -11)/16 = 9/8 ∉ОДЗ .
x₂ =(29 +11)/16 = 5/2.
ответ: 2,5.
-------
N3
а) ;
y ' =( (x² +2x)' (3-4x) - (x² +2x)*(3-4x) ') /(3-4x)² =
( (2x+2)(3 -4x) +4(x² +2x)) /(3-4x)² = -2(2x² -3x-3)/(3-4x)².
---
б) ;
y ' =((5x+2)⁴) ' =4*(5x+2)³*(5x+2)' =4*(5x+2)³*5=20(5x+2)³ .
-------
N3
а) а) =(1/6)*x +C.
---
б) =(-1/3 )интеграл( e^(4-3x)d(4-3x) =(-1/3)e^(4-3x) +C.